Ein anderer Weg bei dem Logarithmusunterricht: Ein entwickelndes Unterrichtsexperiment - Várady, Ferenc (Teaching Mathematics and Computer Science, 2014)
In my developmental experiment I tried to fusion the expectations of the Hungarian education and the realistic mathematics education. The duration of this experiment was 33 lectures long. In this article I try to show how were introduced the definition, the rules of logarithm with real life problems and the outcome of the experiment.